Autophagic degradation of the circadian clock regulator promotes ferroptosis. Issue 11 (2nd November 2019) - Liu, Jiao; Yang, Minghua; Kang, Rui; Klionsky, Daniel J.; Tang, Daolin
ABSTRACT: Macroautophagy (hereafter referred to as autophagy) involves a lysosomal degradation pathway and plays a context-dependent role in promoting either cell survival or cell death during stress; excessive or impaired autophagy is implicated in various types of cell death. In particular, lipid peroxidation-associated ferroptosis has recently been recognized as a type of autophagy-dependent cell death, but the mechanisms involved remain largely obscure. Our recent findings demonstrate that clockophagy, namely the selective autophagic degradation of the circadian clock regulator ARNTL/BMAL1, promotes ferroptotic cancer cell death in vitro and in vivo . Mechanically, the cargo receptor SQSTM1/p62 is responsible for the autophagic degradation of ARNTL in response to type 2 ferroptosis inducers (e.g., RSL3 and FIN56), but not type 1 ferroptosis inducers (e.g., erastin, sulfasalazine, and sorafenib). Consequently, clockophagy-mediated ARNTL degradation promotes lipid peroxidation and subsequent ferroptosis through blocking HIF1A-dependent fatty acid uptake and lipid storage. These findings highlight a novel type of selective autophagy in regulated cell death. Graphical Abstract: